La gestión de los directivos, el componente denominado la cultura de la evaluación, de la propuesta educativa experimental Bernardina, y el desarrollo académico, de la sección matutina, del Colegio Experimental Bernardo Valdivieso, de la parroquia San Sebastián, del cantón y provincia de Loja, en el período 2010-2011 - Yaguana Tacuri, Ángel Polivio (2013)
This research was general objective, establish the incidence of management and directors component called the culture of evaluation, experimental educational proposal bernardina in the academic development of the morning section, the Experimental College Bernardo Valdivieso, parish of San Sebastian, canton and province of Loja, in the period 2010-2011. The development research was supported by the deductive method, which used it as a tool of scientific knowledge, and information analysis established findings, the inductive, was used to identify science, management analyzed managers , the culture of evaluation and reporting of statistical results, the analytical, served to make the analysis of the answers of the respondents, on matters relating to executive management and evaluation culture by school authorities and then draw conclusions, and, with the synthetic, performed the analysis of the culture of evaluation, which allowed progress, issues and basic relationships understand a whole perspective under investigation. It was concluded that the main institutional objectives are not clearly defined, making it impossible to prioritize and exercise operational management or academic education, teachers, students and parents believe that the incidence of executive management and academic development morning section, focuses on a purely theoretical. It is recommended to consistently manage the relationship between the theoretical and practical structure a training plan and a project which is based on the objectives and goals of the institution, which engages all stakeholders develop effective education.